Maternal obesity and risk of cerebral palsy in children: a systematic review and meta‐analysis. (7th August 2018) - Zhang, Jian; Peng, Linrui; Chang, Qingxian; Xu, Ruoting; Zhong, Nanbert; Huang, Qitao; Zhong, Mei; Yu, Yanhong
Abstract : Aim: Several studies have examined the links between maternal obesity and the risk of cerebral palsy (CP) in children, with inconsistent results. The aim of our study was to investigate whether maternal obesity is associated with increased risk of CP in offspring by using meta‐analysis. Method: PubMed and Web of Science were searched until August 2017. Observational studies relevant to the maternal obesity and risk of CP in children were extracted and compiled. Meta‐analyses were performed for different obesity levels and pooled odds ratios (ORs) and 95% confidence intervals (CIs) were reported. Results: A total of five cohort studies involving 12 324 cases and 7 919 288 participants were included in our meta‐analysis. The pooled crude and adjusted ORs (95% CIs) were 1.65 (1.38–1.98) and 1.51 (1.24–1.84) respectively. Additionally, the pooled OR (95% CI) for CP in offspring in relation to maternal obesity class I (body mass index [BMI] 30.0–34.9), class II (BMI 35.0–39.9), and class III (BMI≥40.0) compared with normal weight during prepregnancy or pregnancy was 1.31 (1.15–1.50), 1.65 (1.34–2.02), and 2.37 (1.91–2.94) respectively. Interpretation: This meta‐analysis demonstrated that increasing grades of maternal obesity are associated with a higher risk of CP in offspring. What this paper adds: Meta‐analysis demonstrates a significant positive association between maternal obesity and the risk of cerebral palsy (CP) in children. Subgroup analysis indicates that higher grades of maternal obesity are associated with increasing risk of CP. What this paper adds: Meta‐analysis demonstrates a significant positive association between maternal obesity and the risk of cerebral palsy (CP) in children. Subgroup analysis indicates that higher grades of maternal obesity are associated with increasing risk of CP. This article is commented on by Dolin on page6 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.